Pengaruh Pembiayaan Mudharabah dan Pembiayaan Musyarakah Terhadap Laba Bersih PT Bank Rakyat Indonesia Syariah Tbk Tahun 2011-2020 - Siti Nuraminah; Wirman Wirman (Peneliti.net, 2023)
increase the level of income earned. This will ultimately increase the net income of the bank will be able to face competition while simultaneously expanding the market and the continuity of the bank's business will be more guaranteed. with an even level of income earned by each product with a not too distant comparison, it will make the bank's position more stable and at the same time optimize profit achievement. This study was designed using quantitative methods. The data collection technique uses secondary data, namely the annual financial statements of PT Bank Rakyat Indonesia Syariah Tbk using three variables, namely two independent variables and one dependent variable. The independent variable or independent variable is mudharabah financing and musyarakah financing, while the dependent variable or dependent variable is the net profit of PT Bank Rakyat Indonesia Syariah Tbk in 2011-2020. Based on the results of the study, partially the independent variable, namely mudharabah financing, has no effect on net income at PT Bank Rakyat Indonesia Syariah Tbk for the 2011-2020 period. Meanwhile, musyarakah financing has a significant and significant effect on net profit at PT Bank Rakyat Indonesia Syariah Tbk for the 2011-2020 period. However, mudharabah financing and musyarakah financing simultaneously or simultaneously have an effect or significant impact on net income at PT Bank Rakyat Indonesia Syariah Tbk for the 2011-2020 period.